Assessment Framework Of Zakat On Real Estate Property Developers In Malaysia - Muhammad Fathullah Al-Haq Muhamad Asni; Ahmad Yusairi Yus; Abdul Aziz Mohammed Abd Allah Al-Shibany (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 3 Page (56-80)